Difference in The Incidence Severe Preeclampsia and Eclampsia between Maternal Age 20-34 Years and >34 Years in dr. Soebandi Hospital Jember - Muhammad Fakhri Ali; Yonas Hadisubroto; Jauhar Firdaus (Journal of Agromedicine and Medical Sciences, 2017)
Maternal Mortality Rate (MMR) in Indonesia is still high. The maternal mortality rate continues to rise due to hypertension, one of which is caused by pre-eclampsia and eclampsia. Many factors cause preeclampsia, including advanced maternal age. The purpose of this study was to determine the effect of advanced maternal age during pregnancy with severe preeclampsia and eclampsia in RSD dr. Soebandi Jember. This study used cross sectional approach using 264 samples were divided into two groups, there are pregnant women aged 20-34 years and >34 years. The results of data analysis using Chi Square for severe preeclampsia and obtained p = 0.015 and OR = 2.494, which means there is a significant difference in comparison severe preeclampsia between gestational age of 20-34 years and >34 years. At the age of 20-34 years from 216 samples found 28 people suffering from severe preeclampsia (12.9%). Whereas at the age of mother> 34 years of 48 people found 13 people (27.1%) suffered severe preeclampsia Results of data analysis obtained eclampsia using Fisher and p = 0.554, which means there are no significant differences in comparison eclampsia between gestational age of 20-34 years and >34 years. At the age of 20-34 years from 216 samples found 3 people suffering from eclampsia (1.38%). While at mother age> 34 years from 48 people found 1 person (2.08%) suffered eclampsia.